ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AKTIVITAS PENGAWASAN DEWAN KOMISARIS PADA PERUSAHAAN GO PUBLIC DI INDONESIA - Restria Wijaya; Nur Cahyonowati (Diponegoro Journal of Accounting, 2014)
This study aims to examine the information about The determinants of Board of Commissioners Monitoring Activity in Indonesia. This study was conducted by using Board of Commissioner meeting frequency as dependent variable. The independent variables are Ownership Concentration, Insider Ownership, Board Size, Independent Commissioner Ratio and the Company Size. This research was conducted by using Multiple Regression as a hypothesis test. Data collection in this study used purposive sampling to non-banking companies listed on the Indonesia Stock Exchange in 2011. There were 73 companies used as sample in this study.Result of this study showed that independent variables which are Insider Ownership and Board size negatively affected Board of Commissioner meeting frequency. The other variable, that is size, positively affected the dependent variable.